1995
DOI: 10.1097/00132586-199504000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Blood Pressure Variability in Resting Conditions

Abstract: The objective of this study was to determine the effect of aging on beat-to-beat blood pressure and pulse interval variability in resting conditions and to determine the effect of aging on the sympathetic and vagal influence on the cardiovascular system by power spectral analysis of blood pressure and pulse interval. We studied three groups of healthy, normotensive subjects: young (10 to 15 years, n=16), adult (20 to 40 years, n=16), and elderly (70 to 90 years, n=25). Beat-to-beat blood pressure was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Breathing frequency was not regulated, but did not differ between young and older groups (18Ϯ2 versus 16Ϯ2 breaths/min, respectively, Pϭ0.49). Cardiovagal baroreflex sensitivity was determined from incremental bolus doses of phenylephrine (25,50, 100, and 200 g) administered at 3-minute intervals. R-R intervals were regressed against the corresponding transient increase in systolic blood pressure (SBP) induced by the phenylephrine bolus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breathing frequency was not regulated, but did not differ between young and older groups (18Ϯ2 versus 16Ϯ2 breaths/min, respectively, Pϭ0.49). Cardiovagal baroreflex sensitivity was determined from incremental bolus doses of phenylephrine (25,50, 100, and 200 g) administered at 3-minute intervals. R-R intervals were regressed against the corresponding transient increase in systolic blood pressure (SBP) induced by the phenylephrine bolus.…”
Section: Methodsmentioning
confidence: 99%
“…14,15,22 Briefly, after a stable 30-minute period, baseline measurements were obtained followed by blockade of N N -cholinergic receptors via continuous intravenous infusion of trimethaphan (Cambridge Laboratories Limited). Complete cardiovascular-autonomic blockade was documented by absence of a change in heart rate in response to bolus injection of phenylephrine (25,50, and/or 100 g). After a 20-minute washout period, baseline measurements were repeated.…”
Section: Protocolmentioning
confidence: 99%
“…7,8 In the elderly, changes in spectral Table 2 Heart rate variability and heart rate in the study groups (rest) components induced by standing were more difficult to determine with a Fast Fourier Transform algorithm, probably as a consequence of the reduced variance and the low signal-to-noise ratio. [9][10][11][12] The effect of aging on beat-to-beat blood pressure (BP), pulse interval variability in resting condition, and sympathetic-parasympathetic influence on cardiovascular system evaluated by of BP and pulse interval power spectral analysis, was determined by Veerman et al 13 In this study pulse interval variability was found blunted with aging; the power of mid-frequency band (systolic and diastolic BPs) was markedly lower in the elderly and so was the power of the high frequency of pulse interval. As regards baroreflex sensitivity, calculated by Fast Fourier Transform, it was affected by aging.…”
Section: Arterial Hypertension and Agingmentioning
confidence: 99%
“…6,9-12 However, Veerman and colleagues 13 reported no change in BP variability with aging. It is thought that the age-related changes in variability are associated with alterations in the baroreflex and sympathetic/ parasympathetic control of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%